An intracellular protein delivery platform based on glutathione-responsive protein nanocapsules. Issue 93 (3rd November 2016) - Li, Jie; Zhang, Linlin; Liu, Yang; Wen, Jing; Wu, Di; Xu, Duo; Segura, Tatiana; Jin, Jing; Lu, Yunfeng; Wang, Hui
Abstract : We reported an efficient strategy for the intracellular delivery of proteins based on assembling proteins with a self-crosslinkable polymer. The disulfide-crosslinking structure enhances the stability of the protein–polymer assembly, and also allows effective dissociation of the assembly in response to glutathione. Abstract : An efficient strategy for the intracellular delivery of proteins was developed based on assembling proteins with a self-crosslinkable polymer. Such a disulfide-crosslinking structure enhances the stability of the protein–polymer assembly, and also allows effective dissociation of the assembly in response to glutathione, which allows effective delivery of various proteins with high intracellular bioactivity.